Functional Predictions of Microbial Communities in Soil as Affected by Long‐term Tillage Practices. Issue 1 (1st December 2017) - Hariharan, Janani; Sengupta, Aditi; Grewal, Parwinder; Dick, Warren A.
Abstract : Core Ideas: Microbial function is important but difficult to assess in soil. An omics‐driven tool, PICRUSt, was used to characterize functions of soil microbial communities. No‐tillage compared with plow tillage was functionally enriched for most nutrient cycles. Many other functions integral to soil health can be explored by the PICRUSt omics approach. Soil microbial communities affect the soil's biological, chemical, and physical properties, but there is still a knowledge gap regarding the long‐term impact of tillage practices on soil microbial dynamics. Additionally, the accurate identification of belowground microbial functions is a topic of active interest. In this study, microbial community profiles and functions in soil from a 50‐plus‐year‐old experiment in Ohio, representing one of the world's longest running comparisons of a plow‐tillage system and a continuous no‐tillage system, were compared. The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) algorithm was used to predict associated functional traits from 16S rRNA gene sequences. Analysis of the sequences revealed a large number of unidentified operational taxonomic units (67%), which is consistent with expectations of the soil ecosystem. Next, we investigated gene and enzyme predictions for nitrogen, sulfur, and methane metabolism and hydrocarbon degradation in soil. Results indicated that no‐tillage was functionally enriched for most nutrient cycles. This study has allowed us to predict distinct functional profiles as a result of legacy land uses. It serves as an example of improved analysis of the functional differences in soil managed by long‐term tillage versus no‐till.